Cattle Grazing Preference among Tetraploid and Diploid Annual Ryegrass Cultivars. Issue 1 (1st January 2014) - Solomon, Juan K. Q.; Macoon, Bisoondat; Lang, David J.; Vann, Rhonda C.; Ward, Stephanie
ABSTRACT: Determination of animal preference in the early stages of the evaluation process of new forages may provide insights into potential animal performance as well as plant responses to grazing. A 2‐yr study was conducted at Raymond, MS, to determine grazing preference of cattle between tetraploid and diploid annual ryegrass ( Lolium multiflorum Lam.) cultivars and its relationship with morphological and chemical characteristics. Treatments were two tetraploid cultivars, Maximus and Nelson, and two diploid cultivars, Marshall and Gulf, arranged in a 4 × 4 Latin square design experiment. Eight Angus crossbred yearling steers ( Bos taurus ) (initial body weight of 320 ± 19 kg) were used to determine grazing preference based on herbage disappearance, the Chesson–Manly (CM) index, and amount of time spent grazing. In both years, herbage disappearance was greater for the tetraploid (1380 kg ha −1 ) than diploid cultivars (895 kg ha −1 ), with greater CM index for the tetraploid than for the diploid cultivars (8.1 vs. 5.8% in Year 1 and 6.9 vs. 5.5% in Year 2). Also, animals spent about 10% greater time grazing the tetraploid than diploid cultivars during both years. During the first year, the tetraploid cultivars had less neutral detergent fiber (NDF) (556 vs. 589 g kg −1 ) and less acid detergent fiber (ADF) (341 vs. 359 vs. g kg −1 ) than the diploid cultivars and Nelson had greater water‐soluble carbohydrate (WSC) concentration (184 g kg −1 ) than the other three cultivars (152 g kg −1 ). In the second year, NDF, ADF, and WSC were not different among cultivars. Tetraploid cultivars had a greater proportion of leaf than diploid cultivars. The results indicate that cattle showed greater preference for tetraploid cultivars, which appeared to be linked mainly with pregraze herbage mass and the proportion of leaf.